Profil Gliserida, dan Kandungan EPA (Eicosapentaenoat) dan DHA (Docosaheksaenoat) Hasil Hidrolisis Minyak Hati Ikan Cod oleh Lipase Teramobil dari Mucor Miehei - Erryana Martati; Tyas Utami; Pudji Hastuti (agriTECH, 1999)
Hydrolysis of cod liver oil by immobilized lipase from Mucor miehei was studied to observe the hydrolysis level, glycerides profile and EPA (eicosapentaenoic acid) and DHA (docosahexaenoic acid) contents in the form of glycerides and free fatty acid on various hydrolysis temperatures. Enzymatic hydrolysis of cod liver oil was carried out in a waterbath shaker at temperatures ranging from 30-60°C for 48 hours. Up to 12 hours reaction time, higher temperature gave higher hydrolysis level. Reaction time longer than 12 hours did not improve level of hydrolysis and all of them beyond 67%. This result indicated that there was possibility of acyl migration during hydrolysis. Though the hydrolysis level was high, after 48 hours reaction, EPA and DHA contents in the form of free fatty acid were low.